A computational study on the effect of Ni impurity and O-vacancy on the adsorption and dissociation of water molecules on the surface of anatase (101). (January 2020) - Elahifard, Mohammadreza; Heydari, Hajar; Behjatmanesh-Ardakani, Reza; Peik, Bijan; Ahmadvand, Seyedsaeid
Abstract: Ni impurity has been broadly used in the structure of TiO2 to extend the excitation response to the visible region and thus increase the photocatalytic activity. In this study, a full potential density functional theory has been used to study the effect of Ni impurity, substituted on the surface of anatase (101), on the electronic structure, O-vacancy formation energy, charge transfer, and adsorption and dissociation energies of water molecule. To this end, anatase TiO2 (101) surface is simulated and analyzed in its pure, Ni-doped, defective, and defective Ni-doped forms. According to the results, oxygen vacancies and nickel impurities shift the occupied Ti 3d-orbitals and unoccupied Ni 3d-orbitals below the conduction band and inside the band gap, respectively. In addition, Ni impurity reduces the O-vacancy formation energy and increases the water adsorption energy significantly. While the molecular adsorption is preferred on the surface of plain and Ni-doped anatase (101), the adsorption of the dissociated form is more favorable upon O-vacancy development. Simultaneous presence of O-vacancy and Ni impurity creates an occupied defect state inside the band gap, which mainly corresponds to the Ni 3d-orbitals, as well as a positive synergic effect on the surface reactivity of the anatase (101) by increasing the adsorption energy of water especially in dissociated form. This provides OH groups on the surface as the main reactive specious to trigger the photocatalytic process. Graphical abstract: Image 1 Highlights: Both O-vacancy and Ni impurity expand the water adsorption energy releasing a positive synergic effect on the reactivity of the anatase surface. While the molecular adsorption of water is more favorable on the perfect and Ni-doped anatase (101) surface, the dissociated form is preferred upon developing O-vacancy especially simultaneous with Ni impurity.